Stroke, High Blood Pressure and The Renin–Angiotensin–Aldosterone System – New Developments - Atkinson, Jeffrey (Frontiers in Pharmacology, 2011)
This review considers whether a case can be made for a protective effect of inhibitors and blockers of the renin-angiotensin-aldosterone system (RAAS) on the cerebral circulation. It first looks at whether there exists a preferential effect on the cerebral circulation during a drug-induced lowering of high arterial blood pressure and cardiovascular morbi-mortality. It then goes on to consider background studies on the relationship between Inhibition of the RAAS and stroke. This is followed by exploration of possible new directions in the inhibition of the RAAS and its effect on stroke.